DIGITIZATION OF THE BANKING SYSTEM OF THE REPUBLIC OF UZBEKISTAN: PROS AND CONS - Sotvoldiev Alisher (Scholar Express Journals, 2023)
This article discusses the pros and cons of digitalization of the banking system of the Republic of Uzbekistan.
Keywords: Digital banks; data security; qualifications